2017
DOI: 10.4081/aiua.2017.4.253
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for benign prostatic enlargement: The role of lifestyle habits at younger age. The #Controllati2017 initiative study group

Abstract: Objective: The risk factors for benign prostatic enlargement (BPE) are not well understood and particularly few data are available from Italian population. Materials and methods: This was an observational cross sectional study aimed to examine the association between several risk factors and BPE. During the “#Controllati2017” initiative, men aged 18 years or more were invited to attend participating urologic centers for a free of charge visit for counseling about urologic or andrologic conditions. Each partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Our findings may therefore influence health care policy regarding sleep habits and BPH. Given that the prevalence of BPH is higher in the male population and that the risk of BPH increases with the number of risk factors reported by the participants ( 49 ), as different sleep habits are prevalent in current society and can be altered, uncovering the causal relationship between sleep habits and BPH may influence public health policies for early prevention and timely intervention, slowing the onset and progression of the disease to improve the quality of life of patients while reducing the waste of public resources. Third, we found that prevention of BPH through increased exercise time may be ineffective and that efforts should be made to focus on the impact of multiple causes of body size differences on the development and prognosis of BPH.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings may therefore influence health care policy regarding sleep habits and BPH. Given that the prevalence of BPH is higher in the male population and that the risk of BPH increases with the number of risk factors reported by the participants ( 49 ), as different sleep habits are prevalent in current society and can be altered, uncovering the causal relationship between sleep habits and BPH may influence public health policies for early prevention and timely intervention, slowing the onset and progression of the disease to improve the quality of life of patients while reducing the waste of public resources. Third, we found that prevention of BPH through increased exercise time may be ineffective and that efforts should be made to focus on the impact of multiple causes of body size differences on the development and prognosis of BPH.…”
Section: Discussionmentioning
confidence: 99%
“…Parsons et al [ 12 ] measured PV in 422 subjects aged 27–84 by magnetic resonance imaging and found that 91 subjects (21.6%) had benign PE (PV ≥ 40 ml) on the first visit. The diagnostic rate of benign PE among 1902 Italian men aged >18 increased from 9.3% at the age of ≤50 to 58.7% at the age of >60 in a study based on a digital rectal diagnosis by urologists [ 18 ]. Benign PE in those two studies was diagnosed by PV ≥ 40 ml or digital rectal examination, which was inconsistent with the previous autopsy results.…”
Section: Discussionmentioning
confidence: 99%
“…Less clear is the role of these factors on the lifelong risk when they were present at younger age (7). Since 2016 the Italian Urologic Society (SIU, Società Italiana di Urologia) coordinates a huge preventive initiative: the month of Male Urologic Prevention "#Controllati" (8,9). In the framework of this preventive campaign data have been collected on determinants of the risk of prostatic enlargement and ED.…”
Section: Original Papermentioning
confidence: 99%
“…As already discussed in the papers presenting the results of 2016 and 2017 initiative (8,9), the major flaw of this study is that the study population were men voluntarily presenting to the participating centers. The participating centers were not randomly identified among all Italian urologic centers, so they cannot be considered representative of all Italian centers.…”
Section: Limitationsmentioning
confidence: 99%